(untitled) (Acta Scientiarum. Health Sciences, 2025)
The quality of life in patients with breast cancer has improved over the past decade. This study aimed to assess the quality of life in women with lymphedema following treatment for breast cancer. A total of 31 women with posttreatment breast cancer lymphedema, with a mean age of 61.2 years, were evaluated at Clínica Godoy in Brazil. The clinical diagnosis of lymphedema was confirmed using volumetry, perimetry, and InBody S10 bioimpedance. Lymphedema was defined by a volume increase greater than 10% compared to the contralateral limb. All participants were informed about the study and, upon consent, completed the 36-Item Short Form Survey (SF-36) quality-of-life questionnaire with appropriate guidance. Data were recorded in Excel and analyzed using Start Direct. Scores varied widely, ranging from 15 to 100. The lowest score was in the pain domain (15), while the highest median score was in social functioning (87.5); the lowest median score was in physical functioning (50). Based on Fisher’s exact test and median values, no domain showed statistically significant superiority over the others. Women with lymphedema after breast cancer treatment often experience impairment in at least one aspect of quality of life. Identifying these affected domains is essential for effective patient management.